HF propagation results from the Metal Oxide Space Cloud (MOSC) experiment. Issue 6 (1st June 2017) - Joshi, Dev; Groves, Keith M.; McNeil, William; Carrano, Charles; Caton, Ronald G.; Parris, Richard T.; Pederson, Todd R.; Cannon, Paul S.; Angling, Matthew; Jackson‐Booth, Natasha
Abstract: With support from the NASA sounding rocket program, the Air Force Research Laboratory launched two sounding rockets in the Kwajalein Atoll, Marshall Islands in May 2013 known as the Metal Oxide Space Cloud experiment. The rockets released samarium metal vapor at preselected altitudes in the lower F region that ionized forming a plasma cloud. Data from Advanced Research Project Agency Long‐range Tracking and Identification Radar incoherent scatter radar and high‐frequency (HF) radio links have been analyzed to understand the impacts of the artificial ionization on radio wave propagation. The HF radio wave ray‐tracing toolbox PHaRLAP along with ionospheric models constrained by electron density profiles measured with the ALTAIR radar have been used to successfully model the effects of the cloud on HF propagation. Up to three new propagation paths were created by the artificial plasma injections. Observations and modeling confirm that the small amounts of ionized material injected in the lower F region resulted in significant changes to the natural HF propagation environment. Key Points: High‐frequency propagation effects due to an artificial plasma cloud successfully modeled Effects of arbitrary plasma environments shown to be predicted with accuracy by ray‐tracing Ray tracing can be applied to selectively adjust ionospheric models effectively for HF applications